DESKRIPSI SERTIFIKASI KOMPETENSI TUKANG LOKAL DI PROVINSI SUMATERA BARAT - Gusni Vitri; Deni Irda Mazni (Racic : Rab Construction Research, 2018)
The construction regulation desires that every user and service provider is required to hire a construction worker who has a work competency certificate. As one skilled manpower, construction craffs give a significant contribution to the quality of construction works. The Construction Services Development Agency (LPJK) of West Sumatera Province as an organization for the construction service community has an important role in the certification registration of construction craffs. This is a descriptive quantitative research, with primary and secondary data collection from related stakeholders. Analyzes were performed for the data of the number of certification participants in the construction building workers category with architectural classification (TA code), civil classification (code TS) and environment (Code TT) in West Sumatera Province from 2014 until October 2017. The results showed that the number of registered construction craffs during the period as many as 3286 people and only 16.71% of that number who have identity cards domicile in the province of West Sumatra. As many as 83.29% registered construction craffs are from various regions in Indonesia (outside West Sumatra Province). Registration to obtain certificate of competence is mostly done in year 2015.